Eksistensi Uang Elektronik Sebagai Alat Transaksi Keuangan Modern - Rifqy Tazkiyyaturrohmah (IAIN Ponorogo, 2018)
Abstract: This article aims to examine the transformation of money as a means of modern financial payment. In the viewpoint of finance, electronic money is considered sufficient as a requirement of an object that can be functioned into money because it is easily to be stored, carried and not damaged straightforwardly. In Indonesia, electronic money payment have increased significantly. Indonesian Bank reported that the total electronic payment is 1.64 billion rupiah at November 2017. It increased 98% compare to November 2016. I employed descriptive analysis method. The findings showed that the development of startup business in Indonesia also affects on the increasing of electronic money transactions, such as online transportation Go-Jek or Grab. The competition between Grab and Go-Jek is not only about the business of the transport network, but also the competition of electronic money as the main business support of those company. They are struggling to develop their electronic money service, Grab through GrabPay and Go-Jek through Go-Pay. By targeting the mobile community, electronic money products from these two startup companies attract public interest. Indonesian Bank itself continues to encourage the use of electronic non-cash transactions. Several companies especially banking sectors apply electronic money in order to improve the convenience of the electronic money customers. Bank Indonesia also continuously strives to develop the system and rules on electronic financial transactions. Thus, it is expected that public society select electronic money transactions as a tool of payment for the advancement of the global economy in the digital age.Abstrak: Artikel ini bertujuan mengkaji mengenai transformasi uang sebagai alat transaksi keuangan modern. Dalam konsep keuangan, uang elektronik sudah mencukupi sebagai syarat suatu benda yang dapat difungsikan menjadi uang. Seperti mudah disimpan, mudah dibawa, tidak mudah rusak dan lain-lain. Di Indonesia transaksi uang elektronik telah mengalami peningkatan yang signifikan, per-November 2017 saja BI mencatat volume dan nilai transaksi uang elektronik dengan total nominal transaksi Rp.1,64 triliun atau naik 98% dibanding November 2016. Artikel ini menggunakan metode analisis deskriptif. Kesimpulan artikel ini yaitu berkembangnya bisnis startup di Indonesia juga mempengaruhi transaksi uang elektronik semakin meningkat, seperti transportasi online Go-Jek ataupun Grab. Persaingan antara Grab dan Go-Jek tidak hanya seputar bisnis jaringan tranportasi saja, namun juga persaingan uang elektronik sebagai pendukung bisnis utama perusahaan. Grab melalui GrabPay dan Go-Jek melalui Go-Pay berjuang mengembangkan layanan uang elektronik mereka. Dengan menyasar masyarakat mobile, produk uang elektronik dari dua perusahaan startup ini cukup diminati masyarakat. Bank Indonesia sendiri terus mendorong penggunaan dan penerapan transaksi non tunai dengan uang elektronik. Sudah banyak perusahaan perbankan maupun perusahaan lainnya seperti jasa menggunakan uang elektronik, dan untuk meningkatkan kenyamanan para pengguna uang elektronik. Bank Indonesia juga terus berupaya melakukan pengembangan dan perbaikan terkait sistem maupun aturan tentang transaksi keuangan elektronik. Dengan demikian diharapkan transaksi uang elektronik terus menjadi pilihan masyarakat sebagai instrumen transaksi pembayaran demi kemajuan perekonomian global di era digital.